The Role of Endothelium and Endothelium-Derived Relaxation Factors in Nitric Oxide-Induced Aortic Relaxation - QADIR SALIHI, ABBAS B.; AL-HABIB, OMAR A.M. (Science Journal of University of Zakho, 2013)
The endothelium plays a key role in the control of vascular patency and tone. Thus, the main objective of the study was to determine the role of endothelium and its derived relaxation factors in mediating relaxation of rat thoracic aorta, in response to nitric oxide (NO) donor “sodium nitroprusside (SNP)” using PowerLab tissue bath system. Endothelial denudation enhanced relaxation responses of SNP(1X10-8 to 3X10-5 M)with IC50 of5.872X10-8 as compared to control rings with IC50’s of 2.266X10-6M, as well as the maximum relaxation (Emax) for both groups were 106.2±4.95% and 83.13±14.755%, respectively. The relaxation responses to SNP in aortic rings were significantly increased by Indomethacin and Clotrimazole pretreatment with IC50’s of 1.72X10-7 M and 3.314 X10-8M, and Emax were increased to 121.5±5% and 121.1±8.09%, respectively. Whilst, no changes were observed in aortic rings pretreated with L-nitroargininemethylester (L-NAME) and methylene blue. The results of the current study had shown that endothelium denudation and blocking of endothelium derived-relaxation factors enhanced vasodilator effect of NO; this may be account for the role of endothelium in the vasodilatory effects of NO.